Metodização da engenharia diagnóstica para a profilaxia de manifestações patológicas: estudo em habitações sociais - Souza, Mariana Ribeiro Facundo de (2017)
Many symptoms of construction anomalies have appeared in social housebuilding undertaken by contractors certified in PBQP-h, a prerequisite for using governmental housebuilding program funding. Nevertheless, studies relate the high index of occurrences to failures in quality management, mainly related to the constructive processes, concluding that most of the causes come from failures in the service execution. Accordingly, this work aims to structure an Audit Method which, in a systematic way, facilitates inspections during the work execution phase, in order to attest nonconformities in accordance with the technical guidelines of the Diagnostic Engineering and in order to obtain accurate and local information that can proactively feedback a management system, as well as a quality indicator. Therefore, it is organized in two stages: the first one utilises the technique of Documental Research by an Acting Researcher in describing the systematic inspection tool. The second stage of the work aims to validate the Audit Method in which, by conducting a Field Research, audits some housebuilding funded by the governmental program “My Home, My Life”, raising some nonconformities in the execution of critical services. These data are then compared with Technical Assistance data obtained during the first months of dwellings utilization by the users, showing that the building enterprise that obtained worse results in the audits presented higher rates of constructive anomalies and, therefore, leading to the analysis that the application of the Method cyclically promotes effectiveness to quality control, mainly by enabling the prediction and, consequently, the prevention of those occurrences in buildings.